2014
DOI: 10.1021/ef500534r
|View full text |Cite
|
Sign up to set email alerts
|

Structural Behaviors of Waxy Crude Oil Emulsion Gels

Abstract: At low ambient temperatures in offshore environments, the water-in-oil emulsions of waxy crude oil develop a combined structure of wax crystals and water droplets, resulting in gelling and other complicated flow problems which may severely challenge flow assurance of the multiphase production and transportation system. In this study, the viscoelastic and yield behaviors of waxy crude emulsion gels were investigated, and analyses were then made by investigating the roles of wax particles and water droplets. Sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 46 publications
2
30
2
Order By: Relevance
“…1), suggested that the most strong influence is exercised by the shear stress applied during cooling. The aging time after cooling step, which accord to Sun et al (2014), favours a complete wax precipitation, also showed a minor impact, suggesting that 15 minutes is long enough for most wax precipitation. On the other hand, cooling rate, pointed in many studies as an important factor on yield stress of waxy oils (Venkatesan et.…”
Section: Factorial Experimental Designsmentioning
confidence: 91%
“…1), suggested that the most strong influence is exercised by the shear stress applied during cooling. The aging time after cooling step, which accord to Sun et al (2014), favours a complete wax precipitation, also showed a minor impact, suggesting that 15 minutes is long enough for most wax precipitation. On the other hand, cooling rate, pointed in many studies as an important factor on yield stress of waxy oils (Venkatesan et.…”
Section: Factorial Experimental Designsmentioning
confidence: 91%
“…Water-in-crude oil emulsions generally undergo a solgel transition as temperature is decreased, especially for waxy oils (Hemmingsen et al 2005;Visintin et al 2008;Paso et al 2009;Maia Filho et al 2012;Haj-shafiei et al 2013;Barbato et al 2014;Sun et al 2014). The yield stress of these gelled emulsions may be very high (of the order of 1000 Pa), and an accurate and reproducible method for its measurement still lacks (Barbato et al 2014).…”
Section: Water-in-oil Emulsionsmentioning
confidence: 99%
“…The yield stress of these gelled emulsions may be very high (of the order of 1000 Pa), and an accurate and reproducible method for its measurement still lacks (Barbato et al 2014). To the large number of difficulties already found in the determination of the rheological properties of waxy crude oils (Marchesini et al 2012), several other arise, due to many additional factors that influence the gel structure and hence the bulk rheology (Visintin et al 2008;Paso et al 2009;Maia Filho et al 2012;Sun et al 2014). Among these, we can mention the oil composition and molecular weight, drop size distribution, interfacial tension and rheology, salinity, and pH, just to name but a few.…”
Section: Water-in-oil Emulsionsmentioning
confidence: 99%
“…[8] The photocatalytic activity of g-C 3 N 4 can be further enhanced by combination with noble metals (Pd, Ag), [9] carbon spheres, [10] graphene or carbon nanotubes. [11] The metal-free g-C 3 N 4 is a typical n-type semiconductor, which possesses good electronic property as well as high thermal and chemical stability, making it an ideal material for the modification of Cu 2 O. [12] By combining Cu 2 O with g-C 3 N 4 , p-n heterojunction with intimate surface contact can also be formed to obtain highly active photocatalysts.…”
Section: Introductionmentioning
confidence: 99%